2020
DOI: 10.1080/19475683.2020.1739141
|View full text |Cite
|
Sign up to set email alerts
|

Geospatial analyses to determine academic success factors in California’s K-12 education

Abstract: Standardized test scores are often used to measure students' academic success. Although factors that affect student success involve teaching techniques, classroom dynamics, and study skills, there are other factors outside the classroom that could influence students' overall academic performance. Oftentimes, these factors are overlooked or easily deemed uncontrollable by educators. Prior studies have identified and examined such factors; however, for this analysis, we will use Geographic Information Systems (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…An applied sensitivity analysis has shown that the fixed-distance-band method provides the most differentiated spatial picture, allowing all spatial clusters of both the hot-and the cold-spot analysis to appear. This method allows the best-fitting interpretation of traditional mappings of population change rates, is a good option for polygon data when there is a large variation in polygon size ensuring a consistent scale of analysis, and does not apply a deterministic assumption about neighborhood relationships or distances (Chew et al, 2020;Kim and Choi, 2017;Sanchez-Cuervo and Aide, 2013;Sánchez-Martín et al, 2019).…”
Section: Data and Analytical Strategymentioning
confidence: 99%
“…An applied sensitivity analysis has shown that the fixed-distance-band method provides the most differentiated spatial picture, allowing all spatial clusters of both the hot-and the cold-spot analysis to appear. This method allows the best-fitting interpretation of traditional mappings of population change rates, is a good option for polygon data when there is a large variation in polygon size ensuring a consistent scale of analysis, and does not apply a deterministic assumption about neighborhood relationships or distances (Chew et al, 2020;Kim and Choi, 2017;Sanchez-Cuervo and Aide, 2013;Sánchez-Martín et al, 2019).…”
Section: Data and Analytical Strategymentioning
confidence: 99%